TiO2 films organofunctionalized with 2-aminothiazole ligand and adsorbed Pd(II) ions applied in the photocatalytic degradation of phenol in an aqueous medium - Cristante, Valtair M.; Jorge, Sonia M. A.; Valente, Jose P. S.; Saeki, Margarida J.; Florentino, Ariovaldo O.; Padilha, Pedro M. (Elsevier B.V., 2007)
This paper describes the preparation of thin titanium films via sol-gel route and their subsequent chemical modification by anchoring with 2-aminothiazole ligand and Pd(II) ion sorption, aiming to maximize the photocatalytic activity. The material was characterized by diffuse reflectance infrared Fourier transform spectroscopy, ultraviolet and visible spectrometry, X-ray diffractometry, and scanning electronic microscopy. The amount of palladium adsorbed on the film's surface, determined by graphite furnace atomic absorption spectrometry, showed a value of 2.69 x 10(16) atoms CM-2. The photocatalytic tests indicated that the functionalization with 2-aminothiazole and the adsorption of palladium (II) were determinants in the semiconductor's enhanced photocatalytic activity. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: TiO2 films; photocatalysis; 2-aminothiazole; sensitizer